Amplifying voices in the pandemic: a critical analysis of citizen journalism’s emotional narrative during COVID‑19 - Liu, Niwen; Al Imran Yasin, Megat; AlSagoff, Syed Agil; Ng, Chwee Fang; Li, Mengyu (Springer, 2024)
The global outbreak of COVID-19 has not only triggered a public health crisis but also catalyzed a significant shift in the landscape of information dissemination, with citizen journalism emerging as a pivotal force in narrating the pandemic’s multifaceted impact. This study delves into the emotional constructions within citizen journalism, particularly focusing on the narratives shared on the Global Voices platform. Employing Fairclough’s critical discourse analysis framework, we meticulously examine the linguistic strategies, including headline usage, vocabulary, and stylistic elements, that underpin the portrayal of negative emotions during the pandemic. Our analysis reveals how citizen journalists navigate the delicate balance between conveying critical information and the emotional resonance of their narratives, shaping public perception and reaction amidst widespread anxiety, panic, and anger. The emphasis on negative emotions, as delineated through our corpus of reports from January 2020 to July 2022, underscores the significant role of citizen journalism in influencing societal discourse and emotional response during times of crisis. By providing insights into the interplay between language, emotion, and societal dynamics, this research contributes to a deeper understanding of the power dynamics and ideological underpinnings inherent in the citizen journalism landscape during the COVID-19 pandemic. This study not only highlights the critical role of citizen journalism in filling the information gap left by traditional media but also underscores the challenges posed by the rapid dissemination of emotionally charged narratives, paving the way for future research on responsible reporting and the emotional well-being of the audience during health crises.